2020
DOI: 10.3389/fphys.2020.00080
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Wogonin Provides a Novel Treatment of Knee Osteoarthritis

Abstract: Osteoarthritis (OA) is a degenerative joint disease characterized by joint pain, decreased functional mobility, and deformation of articular cartilage and consequentially diminishing quality of life. Wogonin (WG), a compound extracted from the Skullcap Baicalensis plant, has been shown to have anti‐inflammatory effects on the Toll‐like Receptor 4 (TLR‐4) inflammatory pathway and antioxidant properties via Nrf2. We have shown that TLR‐4 is a major receptor for pain in OA. In our study, we examined the pain redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Moreover, it seems that wogonin prevents DNA denaturation, thus contributing to genomic DNA stability [139]. Considering this evidence, the topical application of this nutraceutical was very recently tested in a mouse DMM model of knee OA [140]. The results showed that a modest dose of wogonin in a topical cream improved joint health as shown by significantly decreased pathological scores (cyst-like lesions (CLLs), Osteoarthritis Research Society International (OARSI), and Mankin scores).…”
Section: Wogoninmentioning
confidence: 99%
“…Moreover, it seems that wogonin prevents DNA denaturation, thus contributing to genomic DNA stability [139]. Considering this evidence, the topical application of this nutraceutical was very recently tested in a mouse DMM model of knee OA [140]. The results showed that a modest dose of wogonin in a topical cream improved joint health as shown by significantly decreased pathological scores (cyst-like lesions (CLLs), Osteoarthritis Research Society International (OARSI), and Mankin scores).…”
Section: Wogoninmentioning
confidence: 99%
“…Baicalein orchestrates the arachidonic acid metabolic pathway and suppresses the production of cyclooxygenase, deoxygenase, nuclear factors, and cytokines, thereby exhibiting a potent antipyretic and analgesic effect [30]. Wogonin performs various biological functions, including anti-inflammatory, antiallergic, antioxidant, and antiapoptotic functions [31,32], Figure 6: Bar plot of GO analysis. The top 10 GO entries for biological processes, cellular components, and molecular functions were selected (P < 0:05).…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein orchestrates the arachidonic acid metabolic pathway and suppresses the production of cyclooxygenase, deoxygenase, nuclear factors, and cytokines, thereby exhibiting a potent antipyretic and analgesic effect [ 30 ]. Wogonin performs various biological functions, including anti-inflammatory, antiallergic, antioxidant, and antiapoptotic functions [ 31 , 32 ], and its anti-inflammatory activity may be associated with a reduction in iNOS and COX-2 expression [ 33 ]. Oroxylin A also has anti-inflammatory and antiallergic effects.…”
Section: Discussionmentioning
confidence: 99%
“…S. baicalensis and its extracts have a strong anti-inflammatory function, participate in the regulation of a variety of inflammatory factors, and also have cartilage protection effects [ 52 ]. Baicalin and baicalein treat skin diseases by regulating enzymes and pro-inflammatory factors such as interleukin-6, oxygenase-1, TNF-α, and cell adhesion factors [ 33 , 46 , 53 ].…”
Section: Biological Functions Of S Baicalensismentioning
confidence: 99%